Unique B Cell Differentiation Profile in Tolerant Kidney Transplant Patients. Issue 1 (13th November 2013) - Chesneau, M.; Pallier, A.; Braza, F.; Lacombe, G.; Le Gallou, S.; Baron, D.; Giral, M.; Danger, R.; Guerif, P.; Aubert‐Wastiaux, H.; Néel, A.; Michel, L.; et al.
Abstract Operationally tolerant patients (TOL) display a higher number of blood B cells and transcriptional B cell signature. As they rarely develop an allo‐immune response, they could display an abnormal B cell differentiation. We used an in vitro culture system to explore T‐dependent differentiation of B cells into plasma cells. B cell phenotype, apoptosis, proliferation, cytokine, immunoglobulin production and markers of differentiation were followed in blood of these patients. Tolerant recipients show a higher frequency of CD20+CD24hiCD38hi transitional and CD20+CD38loCD24lo naïve B cells compared to patients with stable graft function, correlating with a decreased frequency of CD20−CD38+CD138+ differentiated plasma cells, suggestive of abnormal B cell differentiation. B cells from TOL proliferate normally but produce more IL‐10. In addition, B cells from tolerant recipients exhibit a defective expression of factors of the end step of differentiation into plasma cells and show a higher propensity for cell death apoptosis compared to patients with stable graft function. This in vitro profile is consistent with down‐regulation of B cell differentiation genes and anti‐apoptotic B cell genes in these patients in vivo. These data suggest that a balance between B cells producing IL‐10 and a deficiency in plasma cells may encourage an environment favorable to the tolerance maintenance.